УЗГОДЖЕННЯ СУМІСНОЇ РОБОТИ ГЕНЕРАТОРА КОРОТКИХ ВИСОКОВОЛЬТНИХ ІМПУЛЬСІВ НАПРУГИ І КАМЕРИ ДЛЯ ОБРОБКИ ВОДИ ІМПУЛЬСНИМ БАР’ЄРНИМ РОЗРЯДОМ - Берека, В.О.; Кондратенко, І.П (Інститут електродинаміки Національної академії наук України, 2021)
A technique for calculating the parameters of a magnetic switch as an element of a generator of short high-voltage pulses of tension to coordinate its compatible work with a water treatment chamber by dint of pulse barrier discharge is shown. The expediency and efficiency of using such a switch as an element that, by shunting, the discharge chamber, discharges the barrier to the arrival of the next voltage pulse has been confirmed. It is proved that with the accepted geometrical dimensions of the discharge chamber and the amplitude of the pulse voltage, provided that the magnetic switch is present that it is possible to increase the practical use of electricity by ~ 40% due to that which was accumulated in the dielectric barrier in one discharge. Ref.10, fig. 5.